Learning the Mathematical Discussion (MD) Pedagogical Model in and from Practice: The Professional Development of Mathematics Teachers in a Technological Environment - Michele Giuliano Fiorentino; Antonella Montone (Education Sciences, 2025)
On the basis of the hypothesis that has emerged from recent research studies, this article discusses the new pedagogical training model for primary school pre-service teachers (PSTs), namely the Meta Discussion on a Pedagogical model (MDPm). The study was conducted with 400 PSTs enrolled in a primary education mathematics course. The MDPm is a collective discussion involving PSTs and their facilitator about the prior teaching experience based on a Mathematical Discussion (MD) model. In this article we try to give a more detailed definition of MDPm by analyzing different examples drawn from a collection of data gathered in the frame of different teacher training experiments. The results indicate that engaging PSTs in both a direct MD and a subsequent reflective meta-discussion leads to enhanced awareness of the teacher’s role and a more robust conceptualization of the MD model. These experiments aimed to help future teachers recognize the characteristics of their instructional actions within a pedagogical model, engaging them actively in their training, in and from practice. In this setting, PSTs assumed a dual role as both students and future teachers. The research has been conducted in a technological environment, which assumed a fundamental role in supporting the processes involved in the teaching experiment. The examples are analyzed through a specific lens aimed at identifying key elements supporting and refining the MDPm, with the aim of more precisely characterizing it.